Vitivinicultura de precisão aplicada a produção e qualidade de uva Pinot noir no Rio Grande do Sul - Zardo, Katia (2009)
Precision agriculture applied to vitiviniculture can bring several advantages to vitis crop production with positive effects on grape and wine quality. This study s objective was to put into practice precision vtiticulture, aiming to improve the administration and management of vinifera grapes. This research was carried out in a commercial vitis cropland with 2.4 ha located in Encruzilhada do Sul (RS) close to RS/BR km 471. In this area, sandy clay loam Palleudult soil prevails. Sampling for the purposes for soil characterisation was carried out in 0-0,2 m depth. The soil attributes determined were: pH, SOM, texture, Ca, Mg, Al, N, MO, K and P, and the plant attributes were: productivity, alcoholic potential and tartaric acid, using a 35 X 35m grid. Data were analyzed through geostatistics by interpolation technique of kriging. The data of yield and enological parameters were obtained by manual harvest in georeferenced points. Grape data were collected during the harvest in 2007 and 2008 seasons. Soil and plant data were submitted to statistical analysis and basic geostatistic. Spatial variability of soil chemical attributes in the area behaved in accordance with the nutrient evaluated. pH showed low variability, clay, Ca, Mg, and N, showed median variability while MO, P and K , a high variability was found, and for Al, very high. In 2007 harvest, tartaric acid and alcoholic potential showed low variability, number of bunches per plant and weight per bunch presented median variability while weight per plant showed high variability. In 2008 harvest, alcoholic potential showed low variability, while tartaric acid, number of bunches per plant, weight per plant, weight per bunch and number of gems showed median variability. The 35 X 35 m sampling grid has shown itself adequate for soil attributes excepting clay, which obtained a 30.06 m distance reach. In 2007 harvest, the alcoholic potential was the plant attribute that showed smaller reach n the area, 18.42 m. In 2008 harvest, all the plant attributes studied showed a below 35 m reach. The correlation analysis has revealed itself significant among nitrogen and alcoholic potential in 2007 harvest. In 2008 harvest, phosphorus and potassium showed significant correlation with alcoholic potential. The comparison of the demand for the application of fertilizer at varied rate, with application at steady rate of lime, phosphorus and potassium was based on the soil sampling. In the case of lime, there was a 700 kg saving of it with varied rate application, the same was not observed with phosphorus and potassium, which would increase the product quantity if implemented this way, this happens because the levels of them in the soil are appropriate. The adoption of precision viticulture can help the wine grower to know better and further the productive area, allowing to improve the quality and quantity of the vineyard.